2009
DOI: 10.1016/j.jcmg.2008.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Microvascular Resistance Index Immediately After Primary Percutaneous Coronary Intervention as a Predictor of the Transmural Extent of Infarction in Patients With ST-Segment Elevation Anterior Acute Myocardial Infarction

Abstract: MVRI measured immediately after primary PCI is a useful predictor for the TEI in patients with anterior acute MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 28 publications
4
54
0
Order By: Relevance
“…Furthermore, age has been identified as a factor that may affect microvascular resistance (4,14). An elevated HMR, as assessed with a dual-sensor guidewire immediately after PCI, has been associated with microvascular dysfunction in patients with STsegment elevation myocardial infarction, and predictive values have been established for extent of transmural infarction and recovery of left ventricular function (2,15,39). HMR may thus be a useful parameter for early risk stratification in patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, age has been identified as a factor that may affect microvascular resistance (4,14). An elevated HMR, as assessed with a dual-sensor guidewire immediately after PCI, has been associated with microvascular dysfunction in patients with STsegment elevation myocardial infarction, and predictive values have been established for extent of transmural infarction and recovery of left ventricular function (2,15,39). HMR may thus be a useful parameter for early risk stratification in patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary microvascular dysfunction has important emerging implications in clinical diagnosis, risk stratification, and prognosis of cardiac patients (3,15,28,39). Assessment of small vessel disease requires quantification of coronary microvascular resistance, especially in the absence of epicardial disease or with a moderate stenosis resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The recently developed novel dual-sensor (pressure and Doppler velocity) guidewire (PressureWire™ Certus, St Jude Medical) may provide more precise information about microvascular damage. 27 Effectiveness of DP Reperfusion therapy is the established treatment for patients with STEMI and its success is evaluated by the TIMI flow grade on the final coronary angiogram. 28 However, clinical studies using contrast echocardiography 29, 30 and Doppler flowmetry 31 have revealed the existence of poor myocardial reperfusion, 32 and those reports reemphasize the importance of restoring microvascular circulation, except for epicardial coronary flow.…”
Section: Distal Protection and Imr In Amimentioning
confidence: 99%
“…This study provides a method to measure NMR without using a velocity wire, which can potentially be used to evaluate microvascular conditions during coronary arteriography. coronary microvasculation CORONARY MICROVASCULAR DYSFUNCTION occurs in a number of myocardial disease states and has important prognostic implications in different clinical settings, including acute coronary syndromes, diabetic coronary disease, hypertrophic cardiomyopathy, and transplant cardiac allograft vasculopathy (25,26,39). Intracoronary physiological techniques have been advocated and several indexes for the assessment of changes in the microcirculatory bed have been proposed (2, 11, 51), such as coronary flow reserve (CFR) (9, 13, 34) and microvascular resistance (MR) (12,39,49).…”
mentioning
confidence: 99%